An on-line routing algorithm of locally protected paths with exact reservations - Jorge, Luísa (2010)
Routing locally protected Label Switched Paths (LSPs) in MultiProtocol Label Switching (MPLS) networks, achieving efficient shared path protection under distributed control and partial information, is a difficult problem. An estimate of the additional protection bandwidth required in every link of the protection paths is deduced from an equivalent parameter defined in the context of global protection. A method for minimal allocation of protection bandwidth in the context of local shared protection will also be proposed. On-line routing algorithms solutions should be obtained in a very short time, therefore an improved version of the heuristic in [1] is presented, resulting in an new version of this on-line routing algorithm of locally protected paths. The performance of the algorithm in [1] and of the proposed algorithm were evaluated, using minimal allocation of protection bandwidth. Experimental results show that the new algorithm has significant advantages regarding the total bandwidth used, the average number of hops of the active path and the probability of the rejection of new requests.